Turtle mimetic soft robot with two swimming gaits. (4th May 2016) - Song, Sung-Hyuk; Kim, Min-Soo; Rodrigue, Hugo; Lee, Jang-Yeob; Shim, Jae-Eul; Kim, Min-Cheol; Chu, Won-Shik; Ahn, Sung-Hoon
Abstract: This paper presents a biomimetic turtle flipper actuator consisting of a shape memory alloy composite structure for implementation in a turtle-inspired autonomous underwater vehicle. Based on the analysis of the Chelonia mydas, the flipper actuator was divided into three segments containing a scaffold structure fabricated using a 3D printer. According to the filament stacking sequence of the scaffold structure in the actuator, different actuating motions can be realized and three different types of scaffold structures were proposed to replicate the motion of the different segments of the flipper of the Chelonia mydas. This flipper actuator can mimic the continuous deformation of the forelimb of Chelonia mydas which could not be realized in previous motor based robot. This actuator can also produce two distinct motions that correspond to the two different swimming gaits of the Chelonia mydas, which are the routine and vigorous swimming gaits, by changing the applied current sequence of the SMA wires embedded in the flipper actuator. The generated thrust and the swimming efficiency in each swimming gait of the flipper actuator were measured and the results show that the vigorous gait has a higher thrust but a relatively lower swimming efficiency than the routine gait. The flipper actuator was implemented in a biomimetic turtle robot, and its average swimming speed in the routine and vigorous gaits were measured with the vigorous gait being capable of reaching a maximum speed of 11.5 mm s −1 .